Simultaneous enhancement of carrier mobility and concentration via tailoring of Al-chemical states in Al-ZnO thin films - Manish Kumar (2018)
© 2015 AIP Publishing LLC. Simultaneously achieving higher carriers concentration and mobility is a technical challenge against up-scaling the transparent-conductive performances of transparent-conductive oxides. Utilizing one order higher dense (∼1 × 1011cm-3) plasmas (in comparison to the conventional direct current plasmas), highly c-axis oriented Al-doped ZnO films have been prepared with precise control over relative composition and chemical states of constituting elements. Tailoring of intrinsic (O vacancies) and extrinsic (ionic Al and zero-valent Al) dopants provide simultaneous enhancement in mobility and concentration of charge carriers. Room-temperature resistivity as low as 4.89 × 10-4Ω cm along the carrier concentration 5.6 × 1020cm-3is obtained in 200 nm thick transparent films. Here, the control of atomic Al reduces the charge trapping at grain boundaries and subdues the effects of grain boundary scattering. A mechanism based on the correlation between electron-hole interaction and carrier mobility is proposed for degenerately doped wide band-gap semiconductors.